مقارنـة بين مســتويات الكالسـيوم والمغنيزيـوم عند الحوامل وعند حـديثي الولـادة - عابدين بسام; حجوز عقيل; عبُّود منال ابراهيم (Latakia University Journal -Medical Sciences Series, 2019)
شمل البحث 120 امرأةً حاملاً بين 17-40 عاماً ذات حمل وحيد, وفترة حمل طبيعية, حيث تم سحب عينة دموية من كل حامل خلال المخاض الطبيعي, وكذلك تم سحب عينة دموية من الحبل السري للوليد بعد الولادة. وبعد التأكد من كون الوليد بحالة صحية جيدة ووزن طبيعي, قمنا بإجراء اختبارات لمستويات الكالسيوم والمغنيزيوم والفوسفور والفوسفاتاز القلوية والألبومين, على كل من عينة الأم وعينة وليدها, وقمنا بدراسة الفروق في مستويات هذه العناصر بين الأم والوليد. كما درسنا مدى الارتباط بين مستويات هذه العناصر في دم الأم بمستوياتها في دم الوليد، ومدى ارتباط مستويات الكالسيوم بمستويات المغنيزيوم في دم الحامل. كما قمنا بدراسة مدى تأثير تعدد الحمول على مستويات الكالسيوم والمغنيزيوم في دم الحوامل وفي دم المواليد, فكانت النتائج كما يلي: - لوحظ ارتفاع ذو دلالة إحصائية في قيم الكالسيوم والفوسفور والألبومين عند المواليد نسبة للحوامل, بينما لم تلاحظ فروق جوهرية في قيم المغنيزيوم والفوسفاتاز القلوية . - لوحظ ارتباط إيجابي بين مستويات كل العناصر المدروسة عند الأم مع مستوياتها عند الوليد (38% للكالسيوم و39% للمغنيزيوم و45% للفوسفور و40% للألبومين و42% للفوسفاتاز القلوية), كما لوحظ ارتباط إيجابي بين الألبومين وبين كل من الكالسيوم والمغنيزيوم والفوسفور في دم الحوامل, كما وجدنا ارتباطاً إيجابياً بين مستويات الكالسيوم ومستويات المغنيزيوم عند الحوامل بنسبة 27%. - لوحظ انخفاض ذو دلالة إحصائية في قيم الكالسيوم عند الولودات نسبة للخروسات, وكذلك لوحظ انخفاض جوهري في قيم الكالسيوم عند مواليد الولودات نسبة لمواليد الخروسات. بينما لم يلاحظ أي تأثير معتبر لتعدد الحمول على مستويات المغنيزيوم عند الأم أو وليدها. The research included (120) healthy pregnant women between 17-40 years old, without illnesses during their pregnancy, and had only one fetus. We took specimens from the maternal blood at the delivery and from the umbilical cord blood after the normal delivery. After considering the normality of situation and weight of the neonate, we measured the levels of Calcium, Magnesium, Phosphorus, Albumin and Alkaline Phosphatase in maternal and neonatal blood, then we checked those elements’differences between the mother and her neonate. Then we studied the correlation between the mineral elements’levels in maternal blood and umbilical cord blood; and the correlation between the levels of Ca and Mg in the maternal blood. After that, we inspected the effects of the multiparity on the levels of Ca and Mg in maternal and neonatal blood. The results : - The levels of Calcium and Phosphorus and Albumin in blood were remarkably higher in neonates than in mothers, but there weren’t any important differences in Magnesium and Alkaline Phosphatase levels. - We found a positive correlation between all the measured elements levels of the maternal and those of the neonatal blood (38 % for Ca, 39 % for Mg, 45 % for P, 40% for Alb, 42% for Alk.P); and also between Albumin and each of (Ca, Mg, P) in mothers. Besides, we found a positive correlation between Ca and Mg in the maternal blood (27%). - The Ca levels were remarkably lower in the multiparous mother, and also there was an important decrease in Ca levels of her neonate, but there weren’t any effects of the multiparity on the levels of Mg.